Pharmacists as a Source of Advice on Medication Use for Athletes - Kwang Choon Yee; Michael De Marco; Mohammed S. Salahudeen; Gregory M. Peterson; Jackson Thomas; Mark Naunton; Sam Kosari (MDPI AG, 2020)
Background: The World Anti-Doping Agency (WADA) specifies substances that competitive sportspersons are not allowed to take. Some of these substances are contained in common medicines used in everyday medical practice and could be used by athletes by accident. Objectives: This study aimed to explore pharmacists’ knowledge and confidence in guiding athletes about the use of medicines in professional sport. Methods: Registered pharmacists in Australia were invited to participate in an online survey. The survey had five domains and aimed to identify pharmacists’ demographic information, interest in sport, familiarity with WADA guidelines, knowledge on prohibited drug classes, and their opinion about the role of pharmacists in educating athletes on medication use. Descriptive statistics were provided and where appropriate, Chi-square, Mann−Whitney and independent t-test were used to identify potential associations and difference between means. Results: One hundred and thirty-five pharmacists (response rate of 10.6%) completed the survey, with the majority indicating that they were not confident in advising athletes on medication use. Although most respondents believed that pharmacists have a role in the education of athletes to help avoid unintentional doping, only about a quarter indicated that they had sufficient knowledge to advise athletes. About one-half of the respondents could provide fully correct answers when asked to identify the WADA status of some commonly used drugs. Conclusions: The results of the survey indicate that upskilling is required to enable pharmacists in Australia to provide accurate medication advice to professional athletes.